The Influence of Financial Technology on the Advancement of Financial Inclusion in Micro, Small, and Medium Enterprises (MSMEs) in West Java - Hapsari, Ajeng Andriani; Puspitasari, Devy Mawarnie (Accounting Studies and Tax Journal (COUNT), 2024)
The aim of composing this article is to investigate how a whole lot of impact on fintech (risk and investment management, market provisioning, and cashless society) has on financial inclusion (financial knowledge, financial behavior and financial attitudes) in MSMEs in West Java. The research completed is a kind of quantitative study. The population of this research is the MSME industry in West Java with a focus on the usage of archival statistics. This research uses descriptive evaluation and classical assumption exams. The results indicate that the financial technology variables (risk and investment and market provisioning) have no effect on economic inclusion (financial knowledge, financial behavior and financial attitudes) while the fintech variables (cashless society) have an impact on financial inclusion (financial knowledge, financial behavior and financial attitudes).